Innovative laboratory methods for improved tuberculosis diagnosis and drug-susceptibility testing - Mugenyi, Nathan; Ssewante, Nelson; Baruch Baluku, Joseph; Bongomin, Felix; Mukenya Irene, Mutuku; Andama, Alfred; Byakika-Kibwika, Pauline (Frontiers in Tuberculosis, 2024)
The laboratory plays a vital role in the diagnosis of all clinical forms of tuberculosis (TB), from microbiological confirmation of Mycobacterium tuberculosis to drug-susceptibility testing (DST) and treatment monitoring. For many decades, laboratory diagnosis of tuberculosis was based on conventional methods such as smear microscopy, and culture-based methods. However, Mycobacterium tuberculosis is a slow-growing organism, requiring 2-4 weeks or longer for cultures to yield results. Therefore, the evaluation of novel and rapid diagnostic methods has been a priority for research and development. In the beginning of 1990s, molecular-based diagnostics became widely available providing rapid detection, identification, and DST of M. tuberculosis. In this paper, we review some of the new diagnostic methods introduced in the clinical laboratory for the diagnosis of tuberculosis. With the global goal of ending TB as a public health challenge by 2030, enhancing diagnostic capabilities for latent and active TB, along with improving DST, would improve identification and management of cases, reducing transmission rates and curbing the spread of drug-resistant strains. These innovations promise to transform TB control efforts, bringing us closer to eradicating this persistent global health threat.